Discovering and Approaching Mature Happiness: The Implementation of the CasMac Model in a University English Class - Chen, Chih-Hong; Chang, Shu-Mei; Wu, Huei-Min (Frontiers in Education, 2021)
The purpose of this study was to explore the effects of integrating meaning-centered positive education (MCPE) and the second wave positive psychology (PP2.0) into a university English speaking class. The study adopted Wong’s CasMac model of PP2.0 and designed a series of English lessons which aimed to understand the meaning of life through the perspectives of PP2.0 and its focus on MCPE. The participants were 38 university students, with upper-intermediate English proficiency, enrolled in an English speaking class. They participated in the English program for 15 weeks and two hours each week. The quantitative data was collected from survey of the CasMac Measure of Character and analyzed with the paired t-test method, and the qualitative data analysis was collected from students’ weekly learning sheets and journals. The results show that the integration of MCPE and PP2.0 in a university English class is feasible to enhance students’ understanding of mature happiness through the CasMac model and to promote their meanings in life. According to the research findings, it is suggested that the CasMac model can be applied to other fields or other groups who need help to enhance life meaning and improve wellbeing. Particularly under the pandemic of COVID-19, there are people encountering traumas, losses, and sorrows and it is crucial to transform sufferings with the support of approaching mature happiness.